THE ART INCULTURATION OF THE CATHOLIC CHURCH OF THE SACRED HEART OF JESUS GANJURAN AND ITS IMPLICATIONS ON THE SPIRITUALITY OF THE PEOPLE - Tony Anwar Rosidy; Sultan Prasasti, (INTERNATIONAL JOURNAL OF HERITAGE, ART AND MULTIMEDIA (IJHAM), 2024)
The connection between art and religion is found in several places. The Catholic Church of the Sacred Heart of Jesus Ganjuran, Yogyakarta is proof of the cohesion between art and religion in Indonesia. Inculturation is the process of adapting Catholic teachings with local culture, one of which is with art. This study aims to describe the cultural unquenching that occurred in the Catholic Church of the Sacred Heart of Jesus Ganjuran Yogyakarta and its implications on the spirituality of the people. This study uses descriptive qualitative methods with phenomenological approaches. The results showed that the inculturation that occurred resulted in a variety of art activities and art artifacts including Javanese liturgy, liturgical gamelan, Javanese architecture such as pendopo (Javanese pavilion), Javanese versions of Jesus and Mary statues and temples. The spirituality of the people is awakened with the concept of Java which is thick in its worship. Liturgical gamelan is one of the integral components in worship that makes a bond as man's sacred activity with God. The contemporary aspect can be seen from the gamelan classical rules that combine with the choir that forms a new aesthetic. It can touch the people in feeling the presence of God through local culture. The cohesiveness of the value of art and religion can stimulate people to experience the same religious and aesthetic experiences in worship.